An Analysis of Students’ Mathematical Representations in Solving Algebraic Problem of Seventh Grade Based on Gender - Widya Astuti; Fajriani; Rizal; Sukayasa (PRISMA, 2026)
This study aims to describe the mathematical representations of male and female students in solving algebraic problem. This study employed a qualitative descriptive approach. The subjects consisted of two seventh -grade students from SMP Negeri 9 Palu selected through written tests and interviews. The research results show that during the understanding the problem stage, male subjects used verbal, symbolic, and visual representations, whereas female subjects used only verbal and symbolic representations. During the making a plan and carrying out the plan stages, both subjects used symbolic representations by writing down formulas, forming equations, and performing algebraic operations to arrive at the solution. In the looking back stage, the female subject used verbal and symbolic representations more comprehensively by rechecking the solution and providing a coherent explanation, whereas the male subject only wrote down the final conclusion without performing a thorough recheck.